The role of digital consciousness in change management - I. G. Akperov; B. V. Martynov; E. S. Prokopenko (Вестник университета)
The article deals with the problems of change management in the new conditions of superfragility of the BANI-world. Interpretations of the concepts of “transcendental thinking”, “digital consciousness”, “immersiveness” are given. The prerequisites substantiating the idea that transcendental thinking needs to be cultivated in the organisation in order to achieve effective management flexibility are presented. The latter is formed in the broader context of the digital consciousness organisational culture, without which it is impossible to set up the organisation’s staff for a positive perception of immersive management practices and the digital technologies productive use. Barriers to the transformation of organisational processes have been identified. It has been shown that the digital transformation of the organisation increases the resistance on the part of the staff by digital resistance plane, when aversion to any change correlates with a lack of understanding of digital opportunities. The relationship between the conceptual methodologies of digital consciousness and metacognition and the effectiveness of the formation of a change management strategy has been established.